Los delitos sancionados con prisión preventiva y la vulneración de las garantías constitucionales en la republica del Ecuador - Saltos Giler, Bolivar Isidro (2014)
The development of this Thesis was carried out based on the thesis plan and methodological points delivered by Quevedo State Technical University, Faculty of Law. In Chapter I, Introduction a summary of the need for Article 534 paragraph 4 is reformed to private offenses punishable by sentence of more than tu year in the Penal Code of Integral freedom was performed. In Chapter II, the background of the research described, Doctrine, Jurisprudence and legislation is taken as main source the Constitution of the Republic of Ecuador, Treaties and International Conventions on Human Rights and the Code of Criminal Integral which will enter into force in the country. In Chapter III made a brief detail on the implementation of the methodology, the methods used, the field -based surveys of citizens, citizens of Canton La Maná, and lawyers in free practice. In Chapter IV tabulating surveys citizens and legal professionals developed. Chapter V consists of conclusions and recommendations. The proposed amendment to the Code of Criminal Integral this will create a modification to the custodial sentences exceeding two years developed in Chapter VI